Abreviar (distâncias) na internet, conectar-se ao mundo (na linguagem) - Fusca, Carla Jeanny [UNESP]; Komesu, Fabiana [UNESP]; Tenani, Luciani Ester [UNESP] (UNISINOS - Universidade do Vale do Rio Dos Sinos, 2011)
This article aims to investigate the abbreviations used on chats by web-surfers between 15 and 20 years old. The material consists of two virtual conversations of about 60 minutes each. We believe that this linguistic process occurs due to the physical distance that separates affectively the web-surfers by modifying already said utterances in written practices characterized by short time of interaction. This abbreviation process, known as a characteristic of the so called internetês, is not considered as a simple attempt to cut the words, but as a resource that presents linguistics' regularity. Therefore, the theory of phonological syllable is used as a tool in order to verify the process that forms possible abbreviations used on chats. It is believed that, based on the study of the syllable structure, the choice of the graphemes abbreviation may be assessed based on the writing heterogeneity, since the writer might not only use oral/spoken practices but also literate/written ones so as to produce utterances that emerge in the contemporaneity.
Abbreviate (distances) on the internet, connect to the world (in language)
Keywords: Abbreviation; Heterogeneity; Internet; Literacy; Syllable